PENDIDIKAN ISLAM SEBAGAI SALURAN MOBILITAS SOSIAL - Zaimudin - - (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This article is an attempt by the author to observe the phenomenon of social mobility as the effect of Islamic education which is carried out so far. For this purpose the authors conduct a conceptual study on the development of education in the perspective of sociology, with the Qur'an as the foundation of the development of Islamic education as intended. Social mobility is essentially a movement of a person or group of people, both vertical and horizontal, to be an important point discussed in this article. In this case, there are at least three important roles that Islamic education carries. First, Islamic education as the foundation for social mobility. Secondly, Islamic education as a foundation for social stratification changes. Third, Islamic education as a channel for the movement of social mobility.